2018
DOI: 10.1136/bmjoq-2017-000204
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum quality improvement strategy for increasing long-acting contraception uptake at a University Hospital in Haiti

Abstract: To address the gap in the uptake of long-acting contraception (LAC) methods among high-risk postpartum women who fail to return for a family planning method at HôpitalUniversitaire de Mirebalais in the Central Plateau Department of Haiti, contraceptive implant trainings were held for providers on the Labour and Delivery, Post-Partum and Internal Medicine inpatient wards.A very high maternal mortality rate affects large numbers of women in Haiti; however, contraceptive use can reduce maternal mortality signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Conversely, its lack of accessibility (eg, unavailable contraceptive methods, obligation to consult a health professional) may have dissuaded couples from using it 44,51,57,58 . Finally, the place of birth was associated with contraceptive use because women giving birth in a hospital seemed to choose most effective contraceptives such as LARCs more often 29,35,41,47,49,59 …”
Section: Resultsmentioning
confidence: 99%
“…Conversely, its lack of accessibility (eg, unavailable contraceptive methods, obligation to consult a health professional) may have dissuaded couples from using it 44,51,57,58 . Finally, the place of birth was associated with contraceptive use because women giving birth in a hospital seemed to choose most effective contraceptives such as LARCs more often 29,35,41,47,49,59 …”
Section: Resultsmentioning
confidence: 99%
“…This new strategy produced an average improvement of Immediate postpartum LARCs from 5% to 32% of women delivering at the hospital, accepting a long-acting method (including bilateral tubal ligations) by the end of the project and which has proved sustainable at an average of 20% to date. 30 The study done in Kenya Nairobi in 2018, over 16 weeks, showed that the percentage of women using LARCs increased from 17% noted in the baseline study to 83%. The improvement is likely to have been due to the implementation of the options that were derived from the decision matrix.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there were no QI initiatives conducted to improve the unmet need of PPTL. A QI initiative conducted to improve long-term contraception in postpartum women in Haiti proved successful by increasing the uptake from 5% to 32% [9].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there were no QI initiatives conducted to improve the unmet need of PPTL. A QI initiative conducted to improve long-term contraception in postpartum women in Haiti proved successful by increasing the uptake from 5% to 32% [ 9 ]. Considering the effectiveness of this QI initiative in long-term contraception in postpartum and with the background of barriers to PPTL addressed in the earlier studies, we conducted the QI to improve the unmet need for PPTL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation